1991
DOI: 10.1055/s-2007-1024703
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Steroid Use in Body Builders: An Echocardiographic Study of Left Ventricle Morphology and Function

Abstract: To ascertain the effect of anabolic steroids (AS) on left ventricle size and function, M-mode and 2D echocardiographic evaluation was carried out in 14 body builders at the end of a phase of AS self-administration (8 +/- 3 weeks, mean +/- S.D.) and after a period (9 +/- 2 weeks, mean +/- S.D.) of drug withdrawal, as well as in 14 other body builders who had never made use of AS, and in 14 sedentary individuals. All the subjects were also examined anthropometrically. Ventricular septal thickness index was sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 6 publications
(10 reference statements)
2
68
1
8
Order By: Relevance
“…1 Hypertension, 2 left ventricular hypertrophy, 3 and dyslipidaemia 4 have all been described. Whilst physical isometric training produces a physiological hypertrophy of the left ventricle, 5 it has been found that androgenic hormone use in the context of weight training produces pathological remodelling, 6 with an increase in the fibrous collagen component of the hypertrophied myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hypertension, 2 left ventricular hypertrophy, 3 and dyslipidaemia 4 have all been described. Whilst physical isometric training produces a physiological hypertrophy of the left ventricle, 5 it has been found that androgenic hormone use in the context of weight training produces pathological remodelling, 6 with an increase in the fibrous collagen component of the hypertrophied myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated an increase in left ventricular end diastolic volume, left ventricular mass and/or worsening diastolic function [11][12][13], while other studies demonstrated no cardiovascular changes with anabolic steroid use [14][15][16]. However, in bodybuilding, the doses used are often 10-100 times the therapeutic dose; in one report involving 24 weight lifters, the lowest dose was 350% of the usual therapeutic dose [17].…”
Section: Discussionmentioning
confidence: 99%
“…Poor visualization of the right ventricle, a poorly defined endocardial surface, irregular right ventricular geometry, and limited reproducibility of exercise studies are important limitations of echocardiography in evaluating the left and right ventricle [26]. Cardiac exercise CT has been shown to have excellent sensitivity and specificity for detecting coronary disease and for assessing changes in both right and left ventricles [11][12][13][14][15]27,34]. CT also allows clear apical delineation, and breast shadows, obesity, the diaphragm or bowel do not cause attenuation, and excellent reproducibility has been demonstrated, with interstudy, intraobserver and interobserver variations were 0.01±1.4, 0.06±2.0 and 0.28±2.1% respectively [14,28,29,36].…”
Section: Discussionmentioning
confidence: 99%
“…Common side effects include increased risk of cardiovascular disease, coronary artery disease, harmful changes in cholesterol levels and alterations in the heart structure [52,63,64]. These changes may lead to hypertension, cardiac arrhythmias, congestive heart failure, heart attacks or sudden cardiac death [65].…”
Section: Non Medical Use and Abuse Of Aasmentioning
confidence: 99%